Pengetahuan Mahasiswa Kedokteran Gigi tentang Ergonomi dalam Pencegahan Musculoskeletal Disorders - Nur Salsabilla, Zalfa; Anggraini, Wita; Sulistyowati, Indrani (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Ergonomics in dentistry plays a crucial role in preventing musculoskeletal disorders (MSDs) that may affect practitioners due to non-ideal working postures. Dental students are also at risk of developing MSDs, primarily due to improper ergonomic postures during clinical practice.Understanding ergonomics is essential, particularly for dental students, to ensure the adoption of good working habits early on, thereby reducing the risk of MSDs in the future.. Objectives: To identify the level of knowledge among students regarding dental ergonomics as a preventive measure against musculoskeletal disorders. Methods: This study employed a descriptive observational approach with a cross-sectional design. Data from 301 respondents, collected via online questionnaires. Results: Among the respondents, 40,9% were 20 years old, 83.4% were female, 45.5% of respondents belonged to the class of 2021 of the Dentist Education Study Program, and 86.4% belonged to the Dentist Professional Study Program. It was found that 94.4% of respondents had a high level of knowledge, 5.3% had a moderate level of knowledge, and 0.3% had a low level of knowledge. Conclusion: Most students in the Dental Education Study Program and the Dental Professional Study Program have a high level of knowledge about ergonomics in dentistry.